2012
DOI: 10.3389/fnsys.2012.00055
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal activity patterns of odor-induced synchronized potentials revealed by voltage-sensitive dye imaging and intracellular recording in the antennal lobe of the cockroach

Abstract: In animals, odor qualities are represented as both spatial activity patterns of glomeruli and temporal patterns of synchronized oscillatory signals in the primary olfactory centers. By optical imaging of a voltage-sensitive dye (VSD) and intracellular recording from secondary olfactory interneurons, we examined possible neural correlates of the spatial and temporal odor representations in the primary olfactory center, the antennal lobe (AL), of the cockroach Periplaneta americana. Voltage-sensitive dye imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
5
20
0
Order By: Relevance
“…As an effect of cellular adaptation in ORNs and KCs, odor stimulation (Fig 2 A) results in temporally precise and adaptive responses across all layers of the network (Fig 2 B). The effect of SFA implemented in ORNs is transitive and thus carries over to the postsynaptic PN and LN populations in agreement with experimental observations across species (28)(29)(30)(31).…”
Section: Resultssupporting
confidence: 87%
“…As an effect of cellular adaptation in ORNs and KCs, odor stimulation (Fig 2 A) results in temporally precise and adaptive responses across all layers of the network (Fig 2 B). The effect of SFA implemented in ORNs is transitive and thus carries over to the postsynaptic PN and LN populations in agreement with experimental observations across species (28)(29)(30)(31).…”
Section: Resultssupporting
confidence: 87%
“…As an effect of cellular adaptation in ORNs and KCs, odor stimulation (Fig 2 A) results in temporally precise and adaptive responses across all layers of the network (Fig 2 B). The effect of SFA implemented in ORNs is transitive and thus carries over to the postsynaptic PN and LN populations in agreement with experimental 90 observations across species (Stopfer et al, 2003;Wilson et al, 2004;Bhandawat et al, 2007;Krofczik et al, 2009;Watanabe et al, 2012). In the KC population the background firing rate is very low.…”
Section: Sparse Coding In Space and Timesupporting
confidence: 82%
“…Indeed, using simultaneous dual-electrode intracellular recordings, Lei et al ( 2002 ) showed inter- and intra-glomerular spike synchrony among PNs in response to pheromone blend stimulation. Odor-induced interglomerular synchrony in the AL was also reported in cockroaches using voltage-sensitive-dye imaging methods, suggesting that the synchrony code operates at a broad spatial scale (Watanabe, 2012 ). Moreover, experiments that simultaneously recorded neuronal activity across the glomerular array in M. sexta showed that neurons with the most similar odor response profiles produced the highest degree of coincident spikes (Lei et al, 2004 ).…”
Section: Olfactory Attraction For Monitoring and Trappingmentioning
confidence: 75%